(untitled) (Research, Society and Development, 2023)
Objective: The purpose of this literature review was to review and analyze the most important aspects, covering topics such as: Clinical characteristics, etiology, prevalence and treatment of non-carious cervical lesions (NCCL). Background: NCCL is defined as “the pathological loss of hard tooth substance caused by biomechanical loading forces; such loss is the result of flexing and degradation of enamel and/or dentin at some location distant from the actual point of loading. Caused by the synergistic action of the etiological mechanisms: erosion, abrasion and abfraction. In addition to risk factors such as: decreased pH and salivary quantity, dental morphology, dietary habits and inadequate brushing. The prevalence of NCCL increases with age and they are found mostly on the vestibular surfaces, with premolars and canines being the most affected teeth. The treatment ranges from clinical preventive therapy that focuses on modifying eating habits, stimulating salivary flow, using an appropriate brushing technique and intervention with other branches such as nutrition and psychology. Whereas, clinical therapy is based on diagnosis and is focused on reducing hypersensitivity, improving aesthetics, and restoring lost dental tissue. Material and Methods: A search of the literature related to the etiology, clinical characteristics will be developed. prevalence and treatment of NCCL in different databases. Conclusions: NCCLs are a frequent pathology of a multifactorial nature, where a correct diagnosis is essential for its therapeutic approach.